A review of urban rainwater harvesting in China. Issue 1 (10th January 2023) - Zhou, Jinjun; Pang, Yali; Fu, Guangtao; Wang, Hao; Zhang, Yongxiang; Memon, Fayyaz Ali
Abstract: Over the past 30 years, water security issue in Chinese cities has become increasingly serious, largely due to rapid urbanization, population growth and disproportionate investment in water infrastructure. Urban rainwater harvesting (URWH), a household and community-level rainwater management measure, has been widely used during this period. This study provides a critical review of the policies, methods, technology, construction, implementation and benefits related to URWH in China. We show that URWH in China has gone through three phases over the past 30 years: an initial development phase, a rapid development phase and a sponge city construction phase. URWH research has focused mainly on rainwater harvesting, storage, utilization, management and other technologies, with limited attention to policy and benefit analysis. However, the scale of URWH construction and implementation in China remains small and needs further development. Currently, while URWH assessments cover social, ecological and environmental benefits, the economic benefits need to be further strengthened. The next step in URWH implementation should be to strengthen research and development of policy, legal and design standards. This study provides guidance for the implementation of URWH in Chinese cities and other cities alike in developing countries. HIGHLIGHTS: Urban rainwater harvesting (URWH) in China has been divided into three stages. The construction and development of laws and regulations should be emphasized in China in the future. The construction of URWH projects in China has been uneven. China's URWH construction constitutes government-led investment projects embodying positive social and ecological benefits.